Correlation of GDFT combined with rehabilitation therapy in DNA damage repair of esophageal cancer cells - Yan, Lihua; Ji, Yajun (Frontiers in Genetics, 2023)
Esophageal cancer is a common malignant tumor with a high incidence and a serious threat to human health. The treatment of esophageal cancer is a complex process, which requires the comprehensive use of a variety of treatment methods. At present, the treatment of esophageal cancer mainly includes surgery, radiotherapy, chemotherapy and immunotherapy. The research on the treatment of cancer cells based on Goal directed fluid therapy (GDFT) combined with rehabilitation therapy is the focus of the current society. This paper proposed a study on DNA damage repair of cancer cells based on GDFT combined with rehabilitation therapy, aiming to optimize the traditional treatment of esophageal cancer by using GDFT technology. The algorithm proposed in this paper was an electroencephalogram (EEG) signal optimization algorithm based on combined rehabilitation therapy. Through this algorithm, the EEG signal could be optimized. The algorithm could speed up signal processing, and improve signal reliability and stability by reducing the influence of interference signals and improving the signal to noise ratio. These optimization measures could better help researchers analyze and understand EEG signals, so as to help better study brain functions and diseases. Through the test and investigation on the treatment of cancer cells based on GDFT combined with rehabilitation therapy, the results showed that the blood transfusion volume of GDFT treatment and conventional treatment was 251.5 ml and 288.3 ml respectively. This showed that after GDFT treatment, the input amount of various medical fluids was relatively reduced, and the use of medical fluids was more economical. In addition, their bleeding volumes were 295.2 ml and 324.4 ml, respectively. Urine volume was 382.3 ml and 418.1 ml respectively. This showed that after GDFT treatment, the patient’s blood loss and urine volume were relatively reduced, which has improved the patient’s health. This experiment has proved the excellent ability of GDFT combined with rehabilitation therapy in the treatment of esophageal cancer, and this research result has also proved the excellent medical effect of GDFT technology. Similarly, this paper also provided valuable reference information for the treatment of esophageal cancer.